Moderate-to-Severe Diarrhea and Stunting Among Children Younger Than 5 Years: Findings From the Vaccine Impact on Diarrhea in Africa (VIDA) Study. (19th April 2023) - Nasrin, Dilruba; Liang, Yuanyuan; Powell, Helen; Casanova, Ines Gonzalez; Sow, Samba O; Hossain, M Jahangir; Omore, Richard; Sanogo, Doh; Tamboura, Boubou; Zaman, Syed M A; Antonio, Martin; Jones, Joquina Chiquita M; et al.
Abstract: Background: Stunting affects >20% of children <5 years old worldwide and disproportionately impacts underserved communities. The Vaccine Impact on Diarrhea in Africa (VIDA) Study examined the association between an episode of moderate-to-severe diarrhea (MSD) and the risk of subsequent stunting in children <5 years living in 3 sub-Saharan African countries. Methods: In this prospective, matched, case-control study among children <5 years, data were collected over 36 months from 2 groups. "Children with MSD" visited a health center within 7 days of illness onset experiencing ≥3 loose stools/day plus sunken eyes, poor skin turgor, dysentery, intravenous rehydration, or hospitalization. "Children without MSD" were enrolled from the community within 14 days of the index MSD child; they were diarrhea-free during the previous 7 days and were matched to the index case by age, sex, and residence. Using generalized linear mixed-effects models, we estimated the effect of an MSD episode on odds of being stunted, defined as height-for-age z -scores <−2, at a follow-up visit 2–3 months post-enrollment. Results: The proportion of stunting at enrollment was similar when 4603 children with MSD and 5976 children without MSD were compared (21.8% vs 21.3%; P = .504). Among children not stunted at enrollment, those with MSD had 30% higher odds of being stunted at follow-up than children without MSD after controlling for age, sex, study site, and socioeconomic status (adjusted OR: 1.30; 95% CI: 1.05–1.62: P = .018). Conclusions: Children <5 years in sub-Saharan Africa without stunting experienced an increased likelihood of stunting during 2–3 months following an episode of MSD. Strategies for control of early childhood diarrhea should be integrated into programs intended to reduce childhood stunting. Abstract : Stunting disproportionately impacts young children living in low-income countries. In the VIDA study among children <5 years old living in sub-Saharan Africa, an episode of moderate-to-severe diarrhea conferred a 30% higher odds of becoming stunted during 60 days of follow-up.